MEMBANGUN ETIKA AKADEMIK: PENDIDIKAN DI PERSIMPANGAN DAN TANGGUNG JAWAB - Rahmadhani, Yulia; Bainah; Sa'diah; Rahmanda Aprilia; Azinallah, Muhammad; Syayyidi, Muhammad; Iryani, Eva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Academic ethics constitute a crucial foundation in modern education, which stands at a crossroads between the advancement of digital technology, global competitive pressure, and contemporary moral challenges. This article elaborates the essence of academic ethics as a set of moral principles—such as honesty, integrity, responsibility, fairness, and respect—that govern the behavior of academic communities and prevent violations such as plagiarism, data manipulation, and online cheating. In Indonesia, the unique context of the Merdeka Belajar curriculum and the regulation stipulated in Permendikbud No. 53/2019 demands shared responsibility among institutions (through codes of ethics and monitoring), lecturers/teachers (as role models), students (self-awareness), as well as the government and society (regulation and public campaigns). This approach aims to form a generation that is both knowledgeable and moral, integrating local Pancasila values with the demands of the disruptive era in order to maintain the quality of education and the reputation of educational institutions.